Involvement of Phosphatidylserine and Triacylglycerol in the Response of Sweet Potato Leaves to Salt Stress - Yu, Yicheng; Kou, Meng; Gao, Zhonghui; Liu, Yang; Xuan, Ying; Liu, Yaju; Tang, Zhonghou; Cao, Qinghe; Li, Zongyun; Sun, Jian (Frontiers in Plant Science, 2019)
Lipid remodeling plays an important role in the adaptation of plants to environmental factors, but the mechanism by which lipid remodeling mediates salt stress response remains unclear. In this study, we compared the leaf lipidome of two different sweet potato cultivars upon salinity stress. Salt treatment led to obvious remodeling of the leaf lipidome in both cultivars. Compared with Xu 32 (salt sensitive) leaves, Xu 22 (salt tolerant) leaves generally maintained higher abundance of phospholipids, glycolipids, sphingolipids, sterol derivatives and diacylglycerol under salinity condition. Interestingly, salinity stress significantly increased phosphatidylserine (PS) abundance in Xu 22 leaves by predominantly triggering the increase of PS (20:5/22:6). Furthermore, Xu 32 leaves accumulated higher triacylglycerol (TG) level than Xu 22 leaves under salinity condition. Exogenous application of PS delayed the salt-induced leaf senescence in Xu 32 via reduction of salt-induced K+ efflux and upregulation of plasma membrane (PM) H+-ATPase activity. However, inhibition of TG mobilization in salinized-Xu 22 leaves disturbed the energy and K+/Na+ homeostasis as well as PM H+-ATPase activity. These results demonstrate the alterations in the leaf lipidome of sweet potato under salinity condition, underscoring the importance of PS and TG in mediating salt defensive responses in sweet potato leaves.